Original paper The assessment of microcirculation architecture in keloids and hypertrophic scars: videocapillaroscopy - Nastałek, Magdalena; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Aim: The aim of the study was the evaluation in vivo of the differences between the microcirculatory characteristics of the scars (keloids and hypertrophic scars) and healthy skin. Material and methods : Twenty three patients with keloids and twenty with hypertrophic scars were included in the study, evaluating fifty six scar areas and twenty healthy skin areas by means of contact optical probe videocapillaroscopy. Capillary density, length and capillary distribution pattern (punctiform, reticular, directional) together with the presence of microhemorrhages and neoangiogenesis were studied. Results : Capillary length, capillary distribution pattern and presence of neoangiogenesis were found to be significantly increased in keloids and hypertrophic scars compared with controls. There were also significant differences between scars at the active stage and the ones in the atrophic phase as regards capillary length and the degree of neoangiogenesis. Conclusions : Patients with keloids and hypertrophic scars showed in videocapillaroscopy a variety of microcirculatory changes, often clustered in a characteristic pattern of abnormally oriented, dilated capillaries and neoangiogenesis phenomena. This methodology is highly likely to be of value in the assessment and prognostication of keloids and hypertrophic scars outcome.